Pediatric brain arteriovenous malformation recurrence: a cohort study, systematic review and meta-analysis. (28th September 2021) - Hak, Jean-Francois; Boulouis, Gregoire; Kerleroux, Basile; Benichi, Sandro; Stricker, Sarah; Gariel, Florent; Garzelli, Lorenzo; Meyer, Philippe; Kossorotoff, Manoelle; Boddaert, Nathalie; Vidal, Vincent; Girard, Nadine; et al.
Abstract : Background: Recurrence following obliteration of brain arteriovenous malformations (AVMs) is common in children surgically treated, but recurrences following endovascular (EVT) and radiosurgical approaches are scantily reported. Objective: To analyze the rates and risk factors for AVM recurrence after obliteration in a single-center cohort of children with ruptured AVMs treated with multimodal approaches, and to carry out a comprehensive review and meta-analysis of current data. Methods: Children with ruptured AVMs between 2000 and 2019 enrolled in a prospective registry were retrospectively screened and included after angiographically determined obliteration to differentiate children with/without recurrence. A complementary systematic review and meta-analysis of studies investigating AVM recurrence in children between 2000 and 2020 was aggregated to explore the overall recurrence rates across treatment modalities by analyzing surgery versus other treatments. Results: Seventy children with obliterated AVMs were included. AVM recurrences (n=10) were more commonly treated with EVT as final treatment (60% in the recurrence vs 13.3% in the no-recurrence group, p=0.018). Infratentorial locations were associated with earlier and more frequent recurrences (adjusted relative risk=4.62, 95% CI 1.08 to 19.04; p=0.04). In the aggregate analysis, the pooled rate of AVM recurrence was 10.9% (95% CI 8.7% to 13.5%). Younger age at presentation was associated with more frequent recurrences (RR per year increase, 0.97, 95% CI 0.93 to 0.99; p=0.046). Conclusion: Location of infratentorial AVMs and younger age at presentation may be associated with earlier and more frequent recurrences. The higher rates of recurrence in patients with AVMs obliterated with EVT questions its role in an intent-to-cure approach and reinforces its position as an adjunct to surgery and/or radiosurgery.